Race, transnationalism, and nineteenth-century American literary studies - Levine, Robert S. (Robert Steven), 1953- (Cambridge University Press, 2017)
"Inspired by Toni Morrison's call for an interracial approach to American literature, and by recent efforts to globalize American literary studies, Race, Transnationalism, and Nineteenth-Century American Literary Studies ranges widely in its case-study approach to canonical and non-canonical authors. Leading critic Robert S. Levine considers Cooper, Hawthorne, Stowe, Melville, and other nineteenth-century American writers alongside less well known African American figures such as Nathaniel Paul and Sutton Griggs. He pays close attention to racial representations and ideology in nineteenth-century American writing, while exploring the inevitable tension between the local and the global in this writing. Levine addresses transatlanticism, the Black Atlantic, citizenship, empire, temperance, climate change, black nationalism, book history, temporality, Kantian transnational aesthetics, and a number of other issues. The book also provides a compelling critical frame for understanding developments in American literary studies over the past twenty-five years"--